1997
DOI: 10.1136/bmj.315.7119.1338
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial of octreotide for long term management of cirrhosis after variceal haemorrhage

Abstract: Objective: To assess the efficacy of long term octreotide as adjuvant treatment to programmed endoscopic sclerotherapy after acute variceal haemorrhage in cirrhotic portal hypertension. Design: Randomised clinical trial. Setting: University hospital. Subjects: 32 patients with cirrhotic portal hypertension. Interventions: Programmed injection sclerotherapy with subcutaneous octreotide 50 g twice daily for 6 months, or programmed injection sclerotherapy alone. Main outcome measures: Episodes of recurrent varice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…10,11 However, haemodynamic and clinical data are not so consistent when other agents such as octreotide (OCT) are used. The effects of OCT on variceal pressure are controversial as some studies showed a transient decrease, 12 whereas other studies showed no changes or even increases after OCT administration. 13 Vasoactive drugs facilitate endoscopic therapy and improve the efficacy of both EIS and EBL.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 However, haemodynamic and clinical data are not so consistent when other agents such as octreotide (OCT) are used. The effects of OCT on variceal pressure are controversial as some studies showed a transient decrease, 12 whereas other studies showed no changes or even increases after OCT administration. 13 Vasoactive drugs facilitate endoscopic therapy and improve the efficacy of both EIS and EBL.…”
Section: Introductionmentioning
confidence: 99%
“…Since prophylactic octreotide can prevent bleeding in high-risk patients (Jenkins et al, 1997), octreotide LAR might reduce morbidity and mortality through this mechanism. In our trial, gastrointestinal bleeding occurred in four patients (one peptic ulcer, three varices) with a total follow-up approaching 4000 patient-months.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with portal hypertension, octreotide has been used extensively in the management of acute variceal bleeding and other complications, where it reduces portal blood pressure in patients with poor liver function (Jenkins et al, 1997). Although the benefit observed by Kouroumalis et al (1998) may be a direct anticancer effect mediated by specific receptors on HCC cells, its effects on portal hypertension may also reduce the frequency of variceal bleeding.…”
mentioning
confidence: 99%
“…It is of interest, in this regard, that Child C patients were 25% and 28% respectively in the positive studies by Besson and colleagues 13 and by Jenkins and colleagues. 37 Mortality was not influenced by octreotide either in the Cumulative proportions of patients free of rebleeding in the group of 198 patients eligible for ␤-blockers and/or sclerotherapy, according to the randomized treatment: octreotide (n ϭ 97) and placebo (n ϭ 101). The vertical dashed line indicates the 15-day treatment period.…”
Section: Discussionmentioning
confidence: 92%
“…with sclerotherapy for acute variceal bleeding, and more recently Jenkins and colleagues 37 reported a significantly beneficial effect of long-term subcutaneous octreotide associated with sclerotherapy.…”
Section: Discussionmentioning
confidence: 99%